2018
DOI: 10.1161/circinterventions.117.005124
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Channel Size and Tortuosity Predict Retrograde Percutaneous Coronary Intervention Success for Chronic Total Occlusion

Abstract: In retrograde CTO percutaneous coronary intervention, only size and tortuosity of a CC are independent angiographic predictors of CC tracking and technical success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“… 7 Previous studies showed that vessel size, severe collateral tortuosity, side branch at CC tortuosity, inadequate CC exit, and Werner CC score were predictors of retrograde wire CC tracking failure. 11 – 13 In some cases, even if the guidewire passes through, retrograde microcatheter coronary channel tracking remains a challenge. To the best of our knowledge, data on this issue are limited.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previous studies showed that vessel size, severe collateral tortuosity, side branch at CC tortuosity, inadequate CC exit, and Werner CC score were predictors of retrograde wire CC tracking failure. 11 – 13 In some cases, even if the guidewire passes through, retrograde microcatheter coronary channel tracking remains a challenge. To the best of our knowledge, data on this issue are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Dautov et al found that invisible SC were crossed with as much success as larger CCs and faster [23]. A previous study enrolled 216 patients with retrograde CTO in whom PCI was attempted and revealed collateral channel size as a predictor of failure [9]. We found that small size was an independent factor related to failure of GW crossing in SC.…”
Section: Discussionmentioning
confidence: 50%
“…J-channel score includes the vessel size, reverse bend, continuous bends, and corkscrew; it was developed by Nagamatsu et al in 2020 [8]. HLK score consists of vessel size and tortuosity and was developed by Hsien-Li et al [9]. Successful GW crossing was de ned as the guide wire crossing through the SC from the retrograde side and reaching the distal vessel segment.…”
Section: De Nitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrograde approach can be performed via bypass grafts, septal, and epicardial CCs. Every CC 19 should be assessed for size (which is usually evaluated using the Werner classification); 20 tortuosity; angles of entry to and exit; bifurcations; and distance from the CC exit to the distal cap. Septal CC are the safest and should be the default choice whenever possible.…”
Section: Selecting the Collateral Channelmentioning
confidence: 99%